2014
DOI: 10.1021/es5019724
|View full text |Cite|
|
Sign up to set email alerts
|

Multilayered Modeling of Particulate Matter Removal by a Growing Forest over Time, From Plant Surface Deposition to Washoff via Rainfall

Abstract: Airborne fine particulate matter (PM) is responsible for the most severe health effects induced by air pollution in Europe. Vegetation, and forests in particular, can play a role in mitigating this pollution since they have a large surface area to filter PM out of the air. Many studies have solely focused on dry deposition of PM onto the tree surface, but deposited PM can be resuspended to the air or may be washed off by precipitation dripping from the plants to the soil. It is only the latter process that rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 66 publications
(159 reference statements)
1
34
0
1
Order By: Relevance
“…The removal of particulates from the atmosphere by plants occurs throughout the day and year-round through the interception of particulates by plant leaves and bark on trees (Nowak et al 2006). However, certain seasons can have higher rates of particulate matter deposition than others, dependent upon vegetation types, pollutant emissions, and meteorological conditions (Nowak et al 2006;Jim and Chen 2008;Schaubroeck et al 2014). Also, particulate matter capture increases with higher wind speed (Beckett et al 2000a;Nowak et al 2013) and likely changes throughout the day (Nguyen et al 2015).…”
Section: Street Treesmentioning
confidence: 99%
“…The removal of particulates from the atmosphere by plants occurs throughout the day and year-round through the interception of particulates by plant leaves and bark on trees (Nowak et al 2006). However, certain seasons can have higher rates of particulate matter deposition than others, dependent upon vegetation types, pollutant emissions, and meteorological conditions (Nowak et al 2006;Jim and Chen 2008;Schaubroeck et al 2014). Also, particulate matter capture increases with higher wind speed (Beckett et al 2000a;Nowak et al 2013) and likely changes throughout the day (Nguyen et al 2015).…”
Section: Street Treesmentioning
confidence: 99%
“…Trees may mitigate the damaging effects of airborne particles through removal and subsequent lowering of concentrations (Beckett et al 2000, Litschke and Kuttler 2008, Prajapati 2012, Schaubroeck et al 2014). Farmer (1993 reported that trees are biological filters for airborne particles due to their large leaf surfaces relative to ground covered.…”
Section: Effectiveness Of Tree Cover In Reducing Airborne Pollutionmentioning
confidence: 99%
“…Using the itree model, Nowak et al (2013) modeled PM2.5 removal by trees in ten American cities and estimated that annual masses of particles removal ranged from 4.7 t in Syracuse to 64.5 t in Atlanta. Schaubroeck et al (2014) used the canopy interception and PM removal multilayered model (CIPAM) to estimate PM accumulated on a forestry canopy. For a case study in 2010 they estimated that a Scots pine stand in Belgium accumulated about 31 kg PM2.5 ha -1 yr -1 .…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al (2017) used an artificial rainfall simulation system to investigate the influence of rainfall duration and intensity on PM removal from four broad-leaved species, and they detected that final wash off rates in the rainfall events was only 51-70% of initial deposition. In other words, most PM captured by leaves is stored temporarily, since deposited particles on leaf surfaces may be subsequently resuspended from the leaves to the air by wind and rain (Schaubroeck et al 2014). However, PM accumulation in the wax fraction is very important because these particles are trapped permanently (Song et al 2015).…”
Section: Introductionmentioning
confidence: 99%